2018
DOI: 10.3390/polym10050547
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Fabrication of PA66/Surface-Modified Multi-Walled Nanotubes Composite Fibers by Ball Milling and Melt-Spinning

Abstract: PA66/surface-modified multi-walled carbon nanotubes (MWNTs) composite fibers with a better dispersion and a stronger interfacial interaction between MWNTs and polyamide 66 (PA66) matrix were fabricated via the method of ball milling and melt-spinning. The effects of unmodified (U-MWNTs), acid-modified (MWNTs-COOH) and sodium dodecyl benzenesulfonate-modified MWNTs (MWNTs-SDBS) on the physical mechanical and thermal properties of PA66 were investigated. The results show that, the surface modified nanotube can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Regarding CNT/polyamide composites, a number of investigations have been carried out so far [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and majority of them state that CNTs are able to enhance the mechanical performance of polymeric composite systems. Miyagawa et al [36] and Coleman et al [37] produced overall reviews on the mechanical reinforcement of polymers by the use of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding CNT/polyamide composites, a number of investigations have been carried out so far [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and majority of them state that CNTs are able to enhance the mechanical performance of polymeric composite systems. Miyagawa et al [36] and Coleman et al [37] produced overall reviews on the mechanical reinforcement of polymers by the use of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they observed a substantial increase across a wide pH range employing anionic surfactant sodium oleate with carbon black. SDBS is a widely used ionic surfactant, the benzene ring can form π-π conjugate with the sp 2 hybrid bonds on the surface and the polar sulphonate is helpful to disperse in polar water [45]. The interaction of the anionic SDBS will be partly driven by the hydrophobic interaction between the tail groups, the fibre surface, and the repulsion of the negatively-charged head groups [29].…”
Section: Dissolutionmentioning
confidence: 99%
“…Improved distribution of the reinforcing particles leads to a more uniform distribution of the load transfer and an enhanced nanoconfinement effect [15][16][17]. Chien et al have shown that ball-milling induced better dispersion and stronger interfacial interaction of modified multiwalled nanotubes (MWNTs) in a Polyamide-6, 6 (PA66) matrix, which resulted in improved mechanical properties at a lower filler loading [18]. Yang et al have also prepared poly(butylene terephthalate) (PBT) nanocomposites containing modified nano-Sb 2 O 3 particles dispersed by high-speed rotating and high-energy ball-milling.…”
Section: Introductionmentioning
confidence: 99%